(untitled) (Journal of Universal Science Research, 2025)
This paper explores the theoretical and practical foundations of developing learner autonomy in foreign language education. It investigates modern teaching approaches such as task-based and project-based learning, as well as the impact of digital technologies in fostering self-directed learning. The development of autonomy not only supports linguistic proficiency but also promotes critical thinking, self-regulation, and lifelong learning competencies.